Morphological and Micromorphological Investigations of Bidens frondosa L. from Flora of Krasnodar Region, Russia - Vladimir Zinchenko; Fatima Kazbekovna Serebryanaya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Complex morphological and micromorphological studies have been made about bootjack bur (Bidens frondosa) growing on the territory of the Krasnodar region. The lamina is of dorsoventral type. The conduction system has fasciations, three closed collateral bundles, are present near the vein. The leaf is of amphistomatic type, stomatic apparats are present in a small amount. Anticlinical walls of the main cells of the epidermis are strongly flexuose. The lower epidermis if compared to the upper one has a large number of stomatic apparatus of anisocytic type. The trichomes are leggy, represented by multicellular hairs of different shapes and lengths. Micromorphological capabilities of bootjack bur’s transverse section of the caulis and leafstalk have been studied. Received micromorphological data is a fragment of complex pharmacognostic studies of the Bidens kind. For acquiring the anti-allergic medication in the future, it is necessary to make pharma-technological studies and come up with the necessary medical form in the shape of thick extract and also make pharmacological studies in acquiring this medical form.